High‐Temperature Dielectric Relaxation in Pb(Mg1/3Nb2/3)O3–PbTiO3 Single Crystals. Issue 5 (28th February 2013) - Wang, Chunchang; Zhang, Meini; Xia, Wei; Tan, X.
<x xml:space="preserve">Abstract</x> We reported the dielectric properties of Pb(Mg1/3Nb2/3)O3–PbTiO3 single crystal in the temperature range of 300–1073 K and the frequency range of 100 Hz–10 MHz. Our results showed the coexistence of both true‐ and pseudo‐relaxor behaviors in the crystal. The true relaxor behavior related to the paraelectric‐ferroelectric phase transition occurs at~423 K. The pseudo‐relaxor behavior appearing at~773 K was found to be related to oxygen vacancies. Further investigation reveals that the pseudo‐relaxor behavior has fine structure: it contains two oxygen‐vacancy‐related relaxation processes. The low‐temperature relaxation process is a dipolar relaxation created by the hopping motions of the oxygen vacancies, and the high‐temperature relaxation process is a Maxwell‐Wagner relaxation caused by the sample/electrode contacts.